Instantaneous GNSS attitude determination: A Monte Carlo sampling approach. (April 2017) - Sun, Xiucong; Han, Chao; Chen, Pei
Abstract: A novel instantaneous GNSS ambiguity resolution approach which makes use of only single-frequency carrier phase measurements for ultra-short baseline attitude determination is proposed. The Monte Carlo sampling method is employed to obtain the probability density function of ambiguities from a quaternion-based GNSS-attitude model and the LAMBDA method strengthened with a screening mechanism is then utilized to fix the integer values. Experimental results show that 100% success rate could be achieved for ultra-short baselines. Highlights: The Monte Carlo method is used for instantaneous GNSS attitude determination. The method only uses single-frequency carrier phase measurements. 100% success rate of ambiguity resolution is achieved for ultra-short baselines.